Design of a Power Amplification System for S-Band Satellite Applications - Dalbah, Ahmad I. (2021)
A Master of Science thesis in Electrical Engineering by Ahmad Ibrahim R. Dalbah entitled, “Design of a Power Amplification System for S-Band Satellite Applications”, submitted in July 2021. Thesis advisor is Dr. Oualid Hammi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).